Factor XIII Val34Leu Is a Genetic Factor Involved in the Aetiology of Venous Thrombosis - Franco, R F.; Reitsma, P. H.; Lourenço, D.; Maffei, F. H.; Morelli, V.; Tavella, M. H.; Araújo, A. G.; Piccinato, C. E.; Zago, M. A. (Thrombosis and Haemostasis, 1999)
A mutation in the factor XIII gene (FXIII Val34Leu) gene was recently reported to confer protection against myocardial infarction, but its relationship with venous thrombosis is unknown. In addition, a mutation in the 5’-untranslated region of the FXII gene (46 C→T) was identified which is associated with low plasma levels of the protein. Its prevalence in patients with venous thrombosis is also unknown. We investigated the frequency of the FXIII Val34Leu and FXII 46 C→T mutations in 189 patients with deep venous thrombosis and in 187 age-, gender- and race-matched controls. FXIII Val34Leu was detected in 38.6% of the patients and in 41.2% of the controls. Interestingly, homozygosity for the FXIII mutation was found in 1.6% of the patients and in 9.6% of the controls, yielding an odds ratio (OR) for venous thrombosis of 0.16 (95% CI: 0.05-0.5). The OR for hetero-zygotes was 1.1 (95% CI: 0.7-1.7). The FXII 46 C→T mutation was detected in 46.0% of the patients and in 48.6% of the controls. The OR for heterozygotes was 0.9 (95% CI: 0.6-1.4) and for homozygotes the OR was 0.8 (95% CI: 0.3-1.9). Our data indicate that the FXII 46 C→T mutation is unlikely to be a major risk factor for venous thrombotic disease. In contrast, the homozygous state for FXIII Val34Leu is a strong protective factor against venous thrombosis, which emerges as a novel genetic factor involved in the aetiology of thrombophilia.